Associations of activated coagulation factor VII and factor VIIa‐antithrombin levels with genome‐wide polymorphisms and cardiovascular disease risk. (8th December 2017) - Olson, N. C.; Raffield, L. M.; Lange, L. A.; Lange, E. M.; Longstreth, W. T.; Chauhan, G.; Debette, S.; Seshadri, S.; Reiner, A. P.; Tracy, R. P.
Abstract : Essentials: Essentials A fraction of coagulation factor VII circulates in blood as an activated protease (FVIIa). We evaluated FVIIa and FVIIa‐antithrombin (FVIIa‐AT) levels in the Cardiovascular Health Study. Polymorphisms in the F7 and PROCR loci were associated with FVIIa and FVIIa‐AT levels. FVIIa may be an ischemic stroke risk factor in older adults and FVIIa‐AT may assess mortality risk. Summary: Background: A fraction of coagulation factor (F) VII circulates as an active protease (FVIIa). FVIIa also circulates as an inactivated complex with antithrombin (FVIIa‐AT). Objective: Evaluate associations of FVIIa and FVIIa‐AT with genome‐wide single nucleotide polymorphisms (SNPs) and incident coronary heart disease, ischemic stroke and mortality. Patients/Methods: We measured FVIIa and FVIIa‐AT in 3486 Cardiovascular Health Study (CHS) participants. We performed a genome‐wide association scan for FVIIa and FVIIa‐AT in European‐Americans ( n  = 2410) and examined associations of FVII phenotypes with incident cardiovascular disease. Results: In European‐Americans, the most significant SNP for FVIIa and FVIIa‐AT was rs1755685 in the F7 promoter region on chromosome 13 (FVIIa, β = −25.9 mU mL −1 per minor allele; FVIIa‐AT, β = −26.6 pm per minor allele). Phenotypes were also associated with rs867186 located in PROCR on chromosome 20 (FVIIa, β = 7.8 mU mL −1 per minor allele; FVIIa‐AT, β = 9.9 per minor allele). Adjusted for risk factors, a one standard deviation higher FVIIa was associated with increased risk of ischemic stroke (hazard ratio [HR],  1.12; 95% confidence interval [CI], 1.01, 1.23). Higher FVIIa‐AT was associated with mortality from all causes (HR, 1.08; 95% CI, 1.03, 1.12). Among European‐American CHS participants the rs1755685 minor allele was associated with lower ischemic stroke (HR, 0.69; 95% CI, 0.54, 0.88), but this association was not replicated in a larger multi‐cohort analysis. Conclusions: The results support the importance of the F7 and PROCR loci in variation in circulating FVIIa and FVIIa‐AT. The findings suggest FVIIa is a risk factor for ischemic stroke in older adults, whereas higher FVIIa‐AT may reflect mortality risk.